Ingested microplastics: Do humans eat one credit card per week? - Pletz, Martin (Journal of hazardous materials letters, 2022)
Ingested Microplastic (MP) particles can harm the human body. Estimations of the total mass of ingested MP particles correspond to 50 plastic bags per year (Bai et al., 2022), one credit card per week (Gruber et al., 2022), or a median value of 4.1 μg/week for adults (Mohamed Nor et al., 2021). The first two estimations are based on an analysis (Senathirajah et al., 2021) that predicts a total ingested mass of MP particles mi,MP of 0.1–5 g/week. This work revisits and evaluates this calculation and compares its results and methods to Mohamed Nor et al. (2021). Senathirajah combines data of averaged MP particle masses m¯MP from papers that reported MP particle sizes and MP particle counts nMP in shellfish, salt, beer, and water based on other papers that detected MP particles. Combined with the estimated weekly consumption of those consumables, they compute mi,MP. This work raises some serious issues of Senathirajah in the way they combine data and they obtained particle sizes. It concludes that Senathirajah overestimates mi,MP by several orders of magnitude and that mi,MP can be considered as a rather irrelevant factor for the toxic effects of MP particles on the human body. [Display omitted] •The statement that humans ingest 5 g of microplastics per week is reviewed.•The calculation of 0.1 g – 5 g (one credit card) per week contains severe errors.•Great care must be taken when combining microplastic data of different measurements.